2016
DOI: 10.1177/0268355515605670
|View full text |Cite
|
Sign up to set email alerts
|

Changes in levels of apoptosis in the walls of different segments of great saphenous varicose veins

Abstract: VGSV walls were found to have a significant decrease in apoptotic rate compared with that of GSVs. The rate of apoptosis in the intima and media within the upper segment was increased more than the middle and lower segments in the GSVs. Our findings confirm that programmed cell death is down-regulated in primary varicose veins.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 26 publications
0
8
0
Order By: Relevance
“…There is a biologically significant phenotypic overlap with vascular smooth muscle cells isolated from pathologic varicose vein samples, in which expression of Bcl-2 (an apoptosis controlling protein, located at the outer mitochondrial membrane), MMP-1, MMP-2, TIMP-1, and TIMP-2 is dysregulated and proliferation, adhesion, and migration capacities are altered [45]. The number of apoptotic smooth muscle cells increases in the aged venous system as well as in the prevaricose-varicose venous wall [46][47][48][49][50]. In the affected venous networks, hypertrophic and atrophic areas are alternating giving a foundation for massive morphological deformations observed later in life [40,47,51].…”
Section: Smooth Muscle Agingmentioning
confidence: 99%
“…There is a biologically significant phenotypic overlap with vascular smooth muscle cells isolated from pathologic varicose vein samples, in which expression of Bcl-2 (an apoptosis controlling protein, located at the outer mitochondrial membrane), MMP-1, MMP-2, TIMP-1, and TIMP-2 is dysregulated and proliferation, adhesion, and migration capacities are altered [45]. The number of apoptotic smooth muscle cells increases in the aged venous system as well as in the prevaricose-varicose venous wall [46][47][48][49][50]. In the affected venous networks, hypertrophic and atrophic areas are alternating giving a foundation for massive morphological deformations observed later in life [40,47,51].…”
Section: Smooth Muscle Agingmentioning
confidence: 99%
“…Some authors have found a decreased rate of apoptosis in varicose veins in vein segments, 3234 whereas these authors did not analyze vein segments near the SFJ or did not specify the exact investigated segment of the GSV. Only Filis et al.…”
Section: Discussionmentioning
confidence: 99%
“…Usually these smooth muscle cells in the tunica media are located regularly and side-by-side, however, in the varicose veins this usual manner of smooth muscle cells are destructed, and collagen deposits are seen. Although the exact mechanism of this destruction is unknown, failure or down-regulation of programmed cell death, apoptosis, is suggested to be one of the essential factors [11,12].…”
Section: Introductionmentioning
confidence: 99%